2021
DOI: 10.3390/plants10061145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Individual, Simultaneous and Sequential Inoculation of Pseudomonas fluorescens and Meloidogyne incognita on Growth, Biochemical, Enzymatic and Nonenzymatic Antioxidants of Tomato (Solanum lycopersicum L.)

Abstract: This study was conducted on tomato (Solanum lycopersicum cv. K-21) to investigate the bioprotective nature of Pseudomonas fluorescens and its interactive effects with Meloidogyne incognita in terms of growth biomarkers, changes in biochemical attributes and modulation in antioxidant enzymes of the tomato plant. In this study, we grew tomato plants with M. incognita and P. fluorescens in separate pots, simultaneously and sequentially (15 days prior or post) after 15 days of seed sowing. The sequential inoculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Zhou et al (2016) observed for the first time the nematicidal capacity of B. met about M. incognita, however, the strain used in the present assay did not show nematicidal activity in the control of M. enterolobii. Meloidogyne incognita and P. fluorescens in simultaneous inoculations did not efficiently reduce the number of egg mass in tomato root, however, the reduction was greater when the inoculation scheme was P. fluorescens and after 15 days inoculated: M. incognita (Noureldeen et al, 2021). The reproduction factor was higher in tomato plants inoculated with M. javanica followed by inoculation with Paecilomyces lilacinus with an interval of 10 days compared the simultaneous inoculations of the organisms and the inoculation of P. lilacinus 10 days before inoculation with M. javanica (Ganaie & Khan, 2010).…”
Section: Discussionmentioning
confidence: 84%
“…Zhou et al (2016) observed for the first time the nematicidal capacity of B. met about M. incognita, however, the strain used in the present assay did not show nematicidal activity in the control of M. enterolobii. Meloidogyne incognita and P. fluorescens in simultaneous inoculations did not efficiently reduce the number of egg mass in tomato root, however, the reduction was greater when the inoculation scheme was P. fluorescens and after 15 days inoculated: M. incognita (Noureldeen et al, 2021). The reproduction factor was higher in tomato plants inoculated with M. javanica followed by inoculation with Paecilomyces lilacinus with an interval of 10 days compared the simultaneous inoculations of the organisms and the inoculation of P. lilacinus 10 days before inoculation with M. javanica (Ganaie & Khan, 2010).…”
Section: Discussionmentioning
confidence: 84%
“…This is in agreement with the result obtained in the present study. The mechanism of antagonism of rhizosphere bacteria against plant-parasitic nematodes might be due to toxic metabolites or antibiotics 21,22 . Besides, proper management of fungal pathogens by fluorescent pseudomonads is due to the production of toxic metabolites, antibiotics, or siderophores 23,24 .…”
Section: Resultsmentioning
confidence: 99%
“…The change in the content of MDA (a product of lipid peroxidation) serves as an indicator of the level of oxidative damage that a plant has suffered. The reduction in the MDA content following the treatment with the beneficial microorganisms or another sustainable method (the application of humic acid) has been found to correlate with an increase in antioxidant enzymes [ 95 , 114 , 115 ]. Several fungi or bacteria act as BCAs, whether directly by reducing nematode development and/or indirectly by stimulating the plant host defense mechanisms involving mainly antioxidant defense enzymes [ 114 , 116 , 117 ].…”
Section: Discussionmentioning
confidence: 99%